The Effect of N in Organic + Inorganic Liquid Fertilizer on the Activity Ability and Antioxidant Properties of Tea Shoots (Camellia sinensis L. O. Kuntze) in the Rainy and Dry Season - Zakarias Frans Mores Hukom (Faculty of Agriculture, Pattimura University, 2021)
Antioxidant is a term related to the activity ability and properties of the active ingredient. The higher the ability of the antioxidant activity of an active ingredient, the stronger its antioxidant properties are to ward off various free radical compounds due to oxidative stress. The activity ability and antioxidant properties of tea shoots often fluctuate with changing seasons. This study investigated the effect giving nitrogen levels in organic + inorganic liquid fertilizers on the ability of activity and antioxidant properties of tea shoots in different seasons. The experimental design used was a over season complete randomized block design consisting of 5 levels of fertilization concentration in the rainy and dry seasons. The results showed that the application of organic + inorganic liquid fertilizers without the addition of N concentration in the dry season had a significant effect on the antioxidant activity of tea shoots by 88.14%, and 34.15% higher than control plants in the rainy season and 41.81% more. Height of control plants in the dry season. The IC50 value of tea shoots in the rainy season and dry season has very strong antioxidant properties where the order of the antioxidant properties of the control plants < all concentrations of adding N to organic + inorganic liquid fertilizers < concentration of organic + inorganic liquid fertilizers without the addition of N.Keywords: Ability Antioxidant Activity, Organic + Inorganic Liquid Fertilizer, Tea shoots, Antioxidant Properties.